2004
DOI: 10.3171/jns.2004.101.3.0521
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Erdheim—Chester disease by using computerized tomography—guided stereotactic biopsy of a caudate lesion

Abstract: The authors present the case of a 27-year-old woman with Erdheim-Chester disease (ECD) and extensive intracranial involvement, in whom the initial diagnosis of ECD was established based on computerized tomography (CT)-guided stereotactic biopsy of a caudate lesion. Erdheim-Chester disease is a rare non-Langerhans cell histiocytosis of unknown origin that is clinically characterized by bone pain, diabetes insipidus, and exophthalmos. The radiological hallmarks of the disease include symmetrical sclerosis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…2,5,12 This finding is also in contradistinction to the focal mass lesions reported in the supratentorial compartment. 12,14,15,19,20 The final patient demonstrated diffuse FLAIR signal-intensity hyperintensity, similar to findings in a previous report by Bianco et al 21 HPA involvement has been reported as a single micronodular or nodular infundibular stalk mass 5 or thickening of the pituitary stalk. 12 This is similar to the findings in 3 patients in our study who demonstrated linear thickening of the pituitary stalk.…”
Section: Discussionsupporting
confidence: 87%
“…The second novel manifestation of ECD was ependymal enhancement along the lateral ventricle with linear extension inferiorly into the lentiform nucleus. Previous reports have described the presence of focal intra-axial mass lesions of the white matter and basal ganglia 12,14,15 but not this ependymal or linear enhancement. Several targeted treatments, including interferon and imatinib, have recently shown efficacy in ECD.…”
Section: Discussionmentioning
confidence: 79%
“…57,59 Other neurologic involvement is rare but is often the source of significant morbidity. 57,[59][60][61] It may manifest clinically with cerebellar signs, typically lower extremity ataxia, upper motor neuron deficits, and focal neurologic deficits.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…22,30 The most usual features, mainly in intracranial ECD, are dural granulomas in the brainstem or cerebellum with encasement of major vessels, including vertebral and basilar arteries. 4,15,31,32 So far only, 27 patients with intracranial lesions have been documented in ECD (Supplementary Table 1). …”
Section: Erdheim-chester Diseasementioning
confidence: 97%
“…[7][8][9][10][11] Occasionally, intracerebral and dural tumour-like lesions have been reported. [12][13][14][15] It was first described by Jacob Erdheim and William Chester in 1930. 16 However, the term ECD was first coined by Jaffe 17 in 1972 and until 1980, a total of 47 patients with ECD had been reported in the medical literature, with 80 patients reported up to 2004.…”
Section: Erdheim-chester Diseasementioning
confidence: 98%